Studien zur Wertungsforschung vols. 1-36 - Kolleritsch, Otto; Kaufmann, Harald; Hochschule für Musik und Darstellende Kunst in Graz (Graz Vienna Universal, 1968)
The Studien zur Wertungsforschung is dedicated to the philosophical understanding of musical phenomena.Harald Kaufmann founded the book series in Graz (Austria) in 1968. In formulating the title, Kaufmann drew on the Studies in Musicology founded by Guido Adler in 1913. Kaufmann's friend Theodor W. Adorno contributed to the first two volumes (Symposion für Musikkritik and Essays).After Kaufmann's early death in 1970, Otto Kolleritsch continued the series, which is published by Universal Edition (Vienna - London - New York, NY), Austria's only international music publisher. Volume 7 of Studien zur Wertungsforschung (1976) was a major impetus for the now worldwide Zemlinsky renaissance.Since 2004, Andreas Dorschel, Professor of Aesthetics at the Institute for Music Aesthetics at the University of Music and Performing Arts Graz, has given new impetus to the series. Since then, the advisory board of Studies in Valuation Research has included the pianist Alfred Brendel (London), the composer Isabel Mundry (Zurich), the writer Hans-Ulrich Treichel (Leipzig), the sociologist Georgina Born (Cambridge and Oxford), the musicologists Peter Franklin (Oxford) and Birgit Lodes (Vienna) as well as the philosophers Avishai Margalit (Jerusalem) and Lydia Goehr (New York, NY). Roger Scruton was a member until his death. Volume 55 (2013, Jacqueline Fontyn) and Volume 59 (2018, Elizabeth Maconchy) are the first volumes dedicated to the work of female composers. In the case of some volumes, English has been added to German as the language of publication. (https://de.wikipedia.org/wiki/Studien_zur_Wertungsforschung; translated with Deepl.com)
E / D
Keywords: 20th Century (1901-2000); Music history; Music philosophy and esthetics